Teaching foreign language speech basics - Shutova V. D. (Development of modern education system: theory, methodology, experience, 2019)
the article deals with the main types of speech in any language. At school these aspects are one of the most difficult to teach to. That is why it is very important to distinguish all the features and follow basic rules.
Keywords: диалог; средства обучения; монолог; dialogue; monologue; teaching tools; foreign language speech; иноязычная речь